FACTORS INFLUENCING THE REPURCHASE DECISION OF MAO-MAO BEVERAGE PRODUCTS AMONG FEBI STUDENTS AT IAIN SYEKH NURJATI CIREBON - Agisti, Salsabilah Fejrinaningtias; Bakhri, Syaeful; Ulfah, Mariyah; Priambodo, Aji (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
In Indonesia, the beverage business is growing rapidly and experiencing various increasingly innovative changes, this has led to increasingly tight competition in the beverage business. To face this competition, businesses that create distinctive flavors, affordable prices and have a variety of menus can attract consumers in making purchasing decisions. This study aims to analyze the influence of taste, price and menu variations on the repurchase decision of Mao-mao beverage products on students of the Faculty of Economics and Business, IAIN Syekh Nurjati Cirebon. This study uses associative research and a quantitative approach. The population in this study were students of the Faculty of Economics and Business, IAIN Syekh Nurjati Cirebon consisting of 4 majors totaling 2,398 people. The technique used in taking the number of samples was Taro Yamane and obtained a sample of 95 respondents, and Cluster Sampling was used to determine the number of each sample based on the major. Determination of respondent criteria used the Purposive Sampling method. The results of the study showed that the taste variable had a significance value of 0.000 <0.05, meaning that taste had a significant positive effect on repurchase decisions, the price variable had a significance value of 0.000 <0.05, meaning that price had a significant positive effect on repurchase decisions and the menu variation variable had a significance value of 0.023 <0.05, meaning that menu variations had a significant positive effect on repurchase decisions and simultaneously a significance value of 0.000 <0.05, meaning that taste, price and menu variations together had a significant positive effect on repurchase decisions for Mao-Mao drink products among FEBI IAIN Syekh Nurjati Cirebon students.